Gold weights in the treatment of exposure keratopathy – 7-year experience - Nowak-Gospodarowicz, Izabela; Różycki, Radosław; Rękas, Marek (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
Facial nerve palsy and constant exposure of the cornea leads to development of eye-threatening refractory ulcers and perforation. Using gold weights to achieve palpebral fissure closure is a well-established treatment method in such patients. However, there are no papers to assess the effect of the gold weights on the ocular surface. Aim : The aim of this study was to prospectively evaluate the upper eyelid gold weight implants in patients with exposure keratopathy secondary to persistent facial nerve palsy treated in the Department of Ophthalmology of Military Institute of Medicine in Warsaw between 2009 and 2014. Material and methods : 59 patients – 40 women (67.8%) and 19 men (32.2%) at the mean age of 55.5 ± 17.4 years were enrolled. Preoperative assessment involved the evaluation of the protective apparatus of the eye and a full eye examination. The objective treatment outcomes, cosmetic effect and complication rates were assessed during the follow up visits on days 1–10, months 1., 3., 6., 12., 18., 24. and 36. and once a year afterwards. Results : Clinical improvement of the ocular surface in each patient (p< .001) as well as an improvement of the mean best corrected visual acuity from 0.3 to 0.56 (p< .001) were observed postoperatively. Changes in corneal keratometry ranged between 0.25 to 0.5 D. Conclusion : Upper eyelid gold weight implants ensured complete eye opening and closure in most patients with lagophthalmos, whilst avoiding corneal complications or actually improving clinical status of the ocular surface. Early treatment may completely reverse exposure keratopathy. It also improves the best corrected visual acuity, whereas corneal astigmatism is associated with the surgical technique.